2020
DOI: 10.1155/2020/2540687
|View full text |Cite
|
Sign up to set email alerts
|

C1q/TNF-Related Protein 9 Inhibits Coxsackievirus B3-Induced Injury in Cardiomyocytes through NF-κB and TGF-β1/Smad2/3 by Modulating THBS1

Abstract: C1q/TNF-related protein 9 (CTRP9) is implicated in diverse cardiovascular diseases, but its role in viral myocarditis (VMC) is not well explored. This study is aimed at investigating the role and potential mechanism of CTRP9 in VMC. Herein, we found that the peripheral blood collected from children with VMC had lower CTRP9 levels than that from children who had recovered from VMC. H9c2 cardiomyocytes treated with coxsackievirus B3 (CVB3) were applied to establish a VMC model in vitro, and the expression of CTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…THBS1 belongs to the thrombospondin (THBS) family and has biological functions, such as promoting immune activation and enhancing inflammatory response [ 30 ]. We analyzed the expressions of potential molecules associated with the THBS1 pathway using scRNA-seq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…THBS1 belongs to the thrombospondin (THBS) family and has biological functions, such as promoting immune activation and enhancing inflammatory response [ 30 ]. We analyzed the expressions of potential molecules associated with the THBS1 pathway using scRNA-seq.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that THBS1 induces the activation and signaling of TGF-β1 and NF-κB, aggravates liver damage, promotes liver cell death, and ultimately leads to deterioration of liver function [ 27 , 31 ]. In addition, monocytes can also produce a large number of inflammatory mediators through SMAD2 and SMAD3, including dendritic cell (DC)-derived TNFSF13 and IL-18 and T cell-derived IL-2 and IL-4, which can promote the survival, proliferation, and differentiation of B cells [ 30 ]. THBS1 can induce the up-regulation of IL-1β, IL-6, and TNF-α in immune cells, among which IL-6 and TNF-α play an important role in the immune response because they not only can transmit signals but also regulate cell differentiation and apoptosis by activating inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…TIMP3 is an inhibitor of MMPs and the balance of TIMPs/ MMPs is the necessary condition for maintaining the normal ECM remodeling process, while their imbalance would lead to the destruction of the internal structure of the ECM and trigger PTB (78)(79)(80). In addition, THBS1 could induce immune inflammation through downstream TGF-b and NF-kB pathways, which further facilitate the structural disruption of the maternal-fetal interface (81,82). Thus, the DECs derived from the above genes might mediate the essential processes of ECM remodeling and collagen degradation in PTB.…”
Section: Discussionmentioning
confidence: 99%
“…THBS1 encodes an adhesive glycoprotein that mediates cell-to-cell and cell-to-matrix interactions. One study showed that THBS1 induced fatal myocardial atrophy through perK-ATF4-regulated autophagy [34], and another showed that CTRP9 attenuated CVB3-induced injury in cardiomyocytes through NF-κB pathway by modulating THBS1 [35].…”
Section: Discussionmentioning
confidence: 99%